ANALISIS YURIDIS TENTANG PROSES PENGADAAN BARANG/JASA PEMERINTAH SECARA ELEKTRONIK BERDASARKAN PERATURAN PRESIDEN RI NOMOR 54 TAHUN 2010 BESERTA PERUBAHANNYA - SONITEHE TELAUMBANUA (PREMISE LAW JURNAL, 2017)
DOSEN PEMBIMBING:1. Hasim Purba2. Jusmadi Sikumbang3. Mahmul Siregar The Government Procurement Policy Institution as a Non-Ministerial Institution established based on Presidential Regulation No. 106 Year 2007. This research is done through normative juridical approach which is descriptive approach. Sources of research data is obtained from literature and field research. Then analyzed by using qualitative analysis that describes as well as analyzing important data then drawn a conclusion to get the answer from the problems that exist in this case used inductive method.The result of this study that the implementation of the principle of procurement of goods / services that are clean and free of corruption, collusion and nepotism in electronic procurement based on Presidential Regulation No. 54 of 2010 and its changes are; efficient, effective, transparent, open, competitive, fair / non-discriminatory and accountable. However, in its application there are often disharmonization of regulation or overlapping regulation causing legal uncertainty to the implementation.Keywords: e-procurement, government, effective.